A Better Cycle-Breaker for Swiss Democracy? - Hans Gersbach; Rodrigo Casado Noguerales; Samuel Schenk (CESifo GmbH, 2024)
When a counter-proposal is made to an initiative to change the Swiss constitution, the citizenry makes three binary majority choices: the initiative versus the status quo, the initiative versus the counter-proposal, and the status quo versus the counterproposal as a tie-breaker. If there is a cycle, the alternative that beats the status-quo wins. This system invites strategic voting, as exemplified by the 2010 case of the “Ausschaffungsinitiative”. We suggest to break cycles differently by choosing the middle alternative in case of a cycle, which will normally be the counter-proposal. More precisely, we show that there always exists a strong Nash equilibrium in which all citizens vote sincerely. Moreover, the outcome of all alternative strong equilibria with strategic voting is the same as if everybody votes sincerely. We also show that other common cycle-breaker rules cannot achieve the same result.
Keywords: C72; D70; D72; 330; Swiss democracy; three-way referendum; Condorcet Winner; manipulation; information sharing; initiative